2012
DOI: 10.1159/000336558
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Inhibitor Models of Huntington’s Disease and Parkinson’s Disease Induce Zinc Accumulation and Are Attenuated by Inhibition of Zinc Neurotoxicity in vitro or in vivo

Abstract: Background: Inhibition of mitochondrial function occurs in many neurodegenerative diseases, and inhibitors of mitochondrial complexes I and II are used to model them. The complex II inhibitor, 3-nitroproprionic acid (3-NPA), kills the striatal neurons susceptible in Huntington’s disease. The complex I inhibitor N-methyl-4-phenylpyridium (MPP+) and 6-hydroxydopamine (6-OHDA) are used to model Parkinson’s disease. Zinc (Zn2+) accumulates after 3-NPA, 6-OHDA and MPP+ in situ or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 89 publications
0
26
0
Order By: Relevance
“…1B). Hydrogen peroxide (H 2 O 2 ), an ROS known to increase [Zn 2+ ] i by inducing the release of Zn 2+ from zinc-binding proteins (31), significantly reduced cell viability, to a greater extent in ATP13A2 −/− cells ( P < 0.01, Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B). Hydrogen peroxide (H 2 O 2 ), an ROS known to increase [Zn 2+ ] i by inducing the release of Zn 2+ from zinc-binding proteins (31), significantly reduced cell viability, to a greater extent in ATP13A2 −/− cells ( P < 0.01, Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Since then, mitochondrial dysfunction has been recognized as a major contributor to the aetiology of sporadic (25, 26) and familial PD (2730). A recent discovery that zinc accumulation contributes to and conversely, zinc chelation protects against MPTP-induced PD has highlighted a link between zinc and mitochondrial function in the pathogenesis of PD (31). …”
Section: Introductionmentioning
confidence: 99%
“…Because of the need for a more homogenous population of neurons, we utilized the MPP ϩ treatment paradigm in cultured cortical neurons. We and others (8,9,42,43) have shown that MPP ϩ can induce death in non-dopaminergic neurons, such as ceberebellar granule and cortical neurons, by non-dopamine transporter related mechanisms. Importantly, we observed that there was detectable MEF2D binding at the Nur77 promoter basally in neurons (Fig.…”
Section: Nur77 Expression Following Mptp and Relationship Withmentioning
confidence: 88%
“…Application of the iron chelator DFO induces Htt expression in vitro, suggesting a role for Htt in iron homeostasis [196]. The HD-associated mitochondrial toxin 3-nitropropionic acid causes zinc accumulation in vitro [197]. Whether these disruptions in metal homeostasis extend to mitochondria is yet to be confirmed.…”
Section: Huntington's Diseasementioning
confidence: 99%
“…Deficiency of ATP13A2 protein (otherwise known as PARK9, in which mutations are associated with PD) was recently shown to induce mitochondrial zinc accumulation and dysfunction [221], and PD-associated toxins cause zinc accumulation in vitro [197].…”
Section: • • Treatments For Huntington's Diseasementioning
confidence: 99%